A review of the roles of keratinocyte‐derived cytokines and chemokines in the pathogenesis of atopic dermatitis in humans and dogs. Issue 1 (18th July 2016) - Asahina, Ryota; Maeda, Sadatoshi
Abstract : Background: Dysfunction of the physical and chemical barriers of the skin may play roles in the pathogenesis of atopic dermatitis (AD) by facilitating penetration of antigens through the skin and consequently evoking aberrant immune reactions. It is now emerging that keratinocytes are actively involved in cutaneous immune reactions by producing various soluble factors initiated by inflammatory stimuli, including mechanical injury or activation of Toll‐like receptors and protease‐activated receptors. Among the soluble factors, keratinocyte‐derived cytokines and chemokines skew Type 2 helper T (Th2) cell‐dominant immune reactions, with the recruitment of Th2 cells. Objective: To review the roles of keratinocyte‐derived cytokines and chemokines in the pathogenesis of AD in humans and dogs. Conclusion and clinical importance: Keratinocyte‐derived cytokines such as thymus and activation‐regulated chemokine, granulocyte‐macrophage colony stimulating factor, thymic stromal lymphopoietin and interleukin‐33 are involved in the pathogenesis of human AD and possibly in canine AD. These cytokines and chemokines may possibly be used as subjective clinical markers and therapeutic targets for both human and canine AD. Abstract : Background ‐ Dysfunction of the physical and chemical barriers of the skin may play roles in the pathogenesis of atopic dermatitis (AD) by facilitating penetration of antigens through the skin and consequently evoking aberrant immune reactions. It is now emerging that keratinocytes are actively involved in cutaneous immune reactions by producing various soluble factors initiated by inflammatory stimuli, including mechanical injury or activation of Toll‐like receptors and protease‐activated receptors. Among the soluble factors, keratinocyte‐derived cytokines and chemokines skew Type 2 helper T (Th2) cell‐dominant immune reactions, with the recruitment of Th2 cells.Objective ‐ To review the roles of keratinocyte‐derived cytokines and chemokines in the pathogenesis of AD in humans and dogs.Conclusion and clinical importance ‐ Keratinocyte‐derived cytokines such as thymus and activation‐regulated chemokine, granulocyte‐macrophage colony stimulating factor, thymic stromal lymphopoietin and interleukin‐33 are involved in the pathogenesis of human AD and possibly in canine AD. These cytokines and chemokines may possibly be used as subjective clinical markers and therapeutic targets for both human and canine AD.